Gambaran Peminum Tuak (Studi Kasus Pada Warga Sawere Bontoraja Bulukumba) - Andi Rezkiani A.R; Abdul Wahab (Jurnal Berita Sosial, 2022)
Social behavior of drinking palm wine, Sawere residents lead to deviant behavior. This type of qualitative research is descriptive with the approach of sociology of communication and social welfare science. The data sources are primary and secondary, the data collection methods used are observation, interviews and documentation. Data processing and analysis techniques were carried out through four stages, namely: data reduction, data presentation, data comparison analysis, and drawing conclusions. The results of this study describe the behavior of drinking palm wine causing social impacts, among others, the feelings of palm wine drinkers are very unstable, irritable, attention to the environment becomes disturbed, the second negative impact after consuming palm wine is that the drinker will be drunk with alcohol or heavily drunk, the third problem that arises from drinking behavior palm wine is not only felt by palm wine drinkers, even the behavior of drinking palm wine can affect the neighbors around the wine drinker's environment.